Evaluasi sistem pengelolaan sampah di tempat pemrosesan akhir (TPA) Desa Dehegila Kabupaten Pulau Morotai - Muhammad Reza Kusman; Aswan, Marwis; Tandina, Basrul M (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Every human being must produce waste, and it needs to get more serious attention from all parties because waste is a social phenomenon. If waste is not handled properly it can cause environmental problems both directly and indirectly. The direct impact is contracting infectious diseases or skin diseases while the indirect impact from waste is flooding. Along with population growth in a city, the amount of waste produced also increases and if it is not handled properly, it will result in an increasing number of piles of waste. This happens a lot in cities. The purpose of this research is to evaluate waste management in the Dehegila TPA, Morotai Island Regency. The results of this study indicate that the most common characteristics of waste in TPA are inorganic and organic waste, while the waste management used in TPA is open dumping or open management, waste transported to TPA is then carried out by the combustion process. thus causing environmental pollution.